Ablation of kynurenine 3-monooxygenase rescues plasma inflammatory cytokine levels in the R6/2 mouse model of Huntington’s disease - Marie Katrin Bondulich (Nature Portfolio, 2021)
Abstract Kynurenine 3-monooxygenase (KMO) regulates the levels of neuroactive metabolites in the kynurenine pathway (KP), dysregulation of which is associated with Huntington’s disease (HD) pathogenesis. KMO inhibition leads to increased levels of neuroprotective relative to neurotoxic metabolites, and has been found to ameliorate disease-relevant phenotypes in several HD models. Here, we crossed KMO knockout mice to R6/2 HD mice to examine the effect of KMO depletion in the brain and periphery. KP genes were dysregulated in peripheral tissues from R6/2 mice and KMO ablation normalised levels of a subset of these. KP metabolites were also assessed, and KMO depletion led to increased levels of neuroprotective kynurenic acid in brain and periphery, and dramatically reduced neurotoxic 3-hydroxykunurenine levels in striatum and cortex. Notably, the increased levels of pro-inflammatory cytokines TNFa, IL1β, IL4 and IL6 found in R6/2 plasma were normalised upon KMO deletion. Despite these improvements in KP dysregulation and peripheral inflammation, KMO ablation had no effect upon several behavioural phenotypes. Therefore, although genetic inhibition of KMO in R6/2 mice modulates several metabolic and inflammatory parameters, these do not translate to improvements in primary disease indicators—observations which will likely be relevant for other interventions targeted at peripheral inflammation in HD.